'Rights' in the grey area: undocumented border crossers on Lesvos. (April 2015) - Trubeta, Sevasti
The Aegean island of Lesvos is one of the gateways that refugees and undocumented border crossers use for entering European territory. This study deals with two phenomena related to border crossings on Lesvos: first, the efforts of those arriving to be placed in the status of 'administrative detention' in order to receive an expulsion order and then be able to continue their journey; and, second, the activity of the local solidarity network, which initially established an open reception centre for refugees and undocumented immigrants under the umbrella of the civil society, until some activists agreed to put this project under the jurisdiction of the state authorities. In reflecting on these developments, the author addresses two major issues: first, immigration imprisonment as a facet of 'positive power' in the Foucauldian sense, and the possible relationship of the latter to grassroots humanitarian commitment; and, second, specific facets of the current paradigm of immigration imprisonment that can help explain why detention may be interpreted as a right by refugees and immigrants. The author argues that the humanitarianism that arises in the interface of surveillance and the provision of care demonstrates post-bureaucratic features; and further, that the strategy pursued by refugees and undocumented immigrants shows how limited their scope is for asserting any rights, given the intensified augmentation of border surveillance worldwide.